Hopf-Lax formula and generalized characteristics. Issue 2 (25th January 2017) - Hoang, Nguyen
Abstract : We study some differential properties of viscosity solutions for Hamilton–Jacobi equations defined by Hopf-Lax formula A generalized form of characteristics of the Cauchy problem is taken into account the context. Then we examine the strip of differentiability of the viscosity solution given by the function u ( t, x ).